Grab and go alternatif layanan peminjaman buku Pustakalana Children’s Library di masa pandemi - Zahra Fahira Iskandar; Sukaesih Sukaesih; Evi Nursanti Rukmana; Samson CMS (Jurnal Informatio, 2021)
The emergence of the Covid-19 pandemic has changed all life aspects, in which each individual’s activity is now constrained. Limiting activities to gather in one place has a big impact on all life aspects as well. Various sectors in Indonesia, such as logistics, health, offices, information services, education, and other life necessities are forced to find alternative solution in order to survive even if it were done without direct contact. Large-scale social restrictions known as PSBB have an impact on one of the public information services: libraries, one of which is a special libraries that is affected by social policies, especially in the book lending services. One of the special libraries that is affected in this field is the children’s library Pustakalana Children’s Library in Bandung . The research method used was qualitative with case study approach. Data were collected through in-depth interviews and literature review. The respondents interviewed were the director, visitors, and librarian of Pustakalana Children's Library. The result of this research is that Pustakalana Children's Library issued an innovative online book lending service amid Covid-19: Grab and Go. This services was created by the library as a result of large-scale social restrictions in Bandung. Grab and Go is an online-based circulation service, in which users are allowed to borrow books from home by accessing the provided web page. Books that are borrowed then will be sent by Pustakalana to the user’s address. With the Grab and Go service, Pustakalana is still able to carry out circulation activities even in the midst of social restrictions due to Covid-19 and makes it easier to disseminate information, particularly children's books to visitors Pustakalana Children’s Library Bandung.